2020
DOI: 10.23887/jpi-undiksha.v9i1.17667
|View full text |Cite
|
Sign up to set email alerts
|

Online Interactive Multimedia Oriented to HOTS through E-Learning on Physics Material about Electrical Circuit

Abstract: This article explains the development of interactive multimedia which is designed using e-learning. The development technique uses ADDIE model which consists of some stages namely Analyze, Design, Development, Implementation, and Evaluation. The trial subjects in this study were 13 students of Physics Education Department in Universitas Papua who programed basic physics courses in the even semester of 2018-2019. Interactive multimedia validity was obtained based on an assessment sheet filled by 7 validators co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 0 publications
0
27
0
4
Order By: Relevance
“…A study conducted by (Widyaningsih 2020) showed that the developed learning media was categorized valid for all assessment aspects. They were such as layout, navigation, function, and pedagogy.…”
Section: Jurnal Pendidikan Indonesia (Jpi) | 133mentioning
confidence: 99%
“…A study conducted by (Widyaningsih 2020) showed that the developed learning media was categorized valid for all assessment aspects. They were such as layout, navigation, function, and pedagogy.…”
Section: Jurnal Pendidikan Indonesia (Jpi) | 133mentioning
confidence: 99%
“…With the daily increase in student participation in multimedia learning courses, creating and delivering high-quality interactive online and virtual learning content is equally important [22,23].For online learning is effective, developing, designing, and implementing higher multimedia content in online learning classes [24]. Using a standard approach to introduce and develop multimedia in an education system allows students to access and acquire information in a comfortable, interactive environment with easy accessibility to related information [25,26]. Implementing multimedia learning within a given framework can facilitate content creation and benefit from the online as a tool for teaching and learning [27,28].…”
Section: Significance Of Evaluation Education System Using the Multimedia Interfacementioning
confidence: 99%
“…As a result, today's education world has used many internet-based learning processes or what is commonly known as e-learning. E-learning is a learning process that utilizes information technology (Thai, De Wever, & Valcke, 2017;Widyaningsih, Yusuf, Prasetyo, & Istiyono, 2020). With e-learning, learning is packaged to be accessed easily and quickly without being hindered by distance and time.…”
Section: Introductionmentioning
confidence: 99%